A genome‐wide association study reveals that the 2‐oxoglutarate/malate translocator mediates seed vigor in rice. (22nd August 2021) - Li, Wenjun; Yang, Bin; Xu, Jiangyu; Peng, Liling; Sun, Shan; Huang, Zhibo; Jiang, Xiuhua; He, Yongqi; Wang, Zhoufei
SUMMARY: Seed vigor is an important trait for the direct seeding of rice ( Oryza sativa L.). In this study, we examined the genetic architecture of variation in the germination rate using a diverse panel of rice accessions. Four quantitative trait loci for germination rate were identified using a genome‐wide association study during early germination. One candidate gene, encoding the 2‐oxoglutarate/malate translocator ( OsOMT ), was validated for qGR11 . Disruption of this gene ( Osomt mutants) reduced seed vigor, including seed germination and seedling growth, in rice. Functional analysis revealed that OsOMT influences seed vigor mainly by modulating amino acid levels and glycolysis and tricarboxylic acid cycle processes. The levels of most amino acids, including the Glu family (Glu, Pro, Arg, and GABA), Asp family (Asp, Thr, Lys, Ile, and Met), Ser family (Ser, Gly, and Cys), and others (His, Ala, Leu, and Val), were significantly reduced in the mature grains and the early germinating seeds of Osomt mutants compared to wild type (WT). The glucose and soluble sugar contents, as well as adenosine triphosphate levels, were significantly decreased in germinating seeds of Osomt mutants compared to WT. These results provide important insights into the role of OsOMT in seed vigor in rice. Significance Statement: Seed vigor is an important trait for the direct seeding of rice ( Oryza sativa L.); however, its genetic regulation is unclear. Here a genome‐wide association study reveals that a gene encoding the 2‐oxoglutarate/malate translocator mediates seed vigor mainly by modulating amino acid levels and glycolysis and tricarboxylic acid cycle processes in rice.